Analisis Perbandingan Senar Gitar Nilon Berukuran 0,28 - 0,43 Inch Pada Merek Yamaha Dan Fender Untuk Permainan Gitar Teknik Tremolo - Muhamad Rasyid Ridha; Dody Mohamad Kholid; Enry Johan Jaohari (Journal of Mandalika Literature, 2025)
Guitar strings affect the comfort of the guitarist as well as the quality of the sound produced when playing the tremolo technique, which produces a continuous tone. This research aims to analyze the comparison between nylon guitar strings measuring 0.28 – 0.43 inches from the Yamaha and Fender brands, two brands that are widely used by guitarists. The method applied is a comparative descriptive method, with a focus on evaluating the differences in tension, sustain and timbre produced by the two brands. Data was collected through acoustic testing by pairing strings on the same guitar. After installing the strings, a research subject played the first bar of the piece “Recuerdos de la Alhambra” and recorded it using a sound meter application that displays frequency data and graphs. In addition, researchers conducted a survey of 30 users who had used nylon strings from these two brands. The results showed that Yamaha strings have lower tension, which makes it easier for guitarists to play the tremolo technique, as applied in the work "Recuerdos de la Alhambra". In contrast, Fender strings offer the advantage of longer sustain and a more characteristic timbre, making them also suitable for tremolo techniques. This research provides insight into how different string characteristics affect the performance of the tremolo technique and its application in various guitar playing styles.